2021
DOI: 10.35188/unu-wider/2021/942-6
|View full text |Cite
|
Sign up to set email alerts
|

Premature deindustrialization and income inequality in middle-income countries

Abstract: This paper examines the income inequality implications of a ‘premature deindustrialization’ trend in middle-income countries. To identify the premature deindustrialization phase, we arrive at five conditions based on the trends in employment and value-added share of manufacture. Among these five conditions, the first and second examine the deindustrialization pattern in economies. The last three classify the identified deindustrialization phase as premature or not. We apply panel fixed-effects and bootstrap-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Nayyar et al (2021) argued that premature deindustrialization matters in lower-income countries because the prospect of their service-led development is limited. Ravindran and Babu (2021) identified the rise of income inequality with premature deindustrialization in case that workers are absorbed into low-productive and informal market services. Botta et al (2022) found that net capital inflows are as a potential source of premature deindustrialization.…”
Section: Literature Review and Study Contributionsmentioning
confidence: 99%
“…Nayyar et al (2021) argued that premature deindustrialization matters in lower-income countries because the prospect of their service-led development is limited. Ravindran and Babu (2021) identified the rise of income inequality with premature deindustrialization in case that workers are absorbed into low-productive and informal market services. Botta et al (2022) found that net capital inflows are as a potential source of premature deindustrialization.…”
Section: Literature Review and Study Contributionsmentioning
confidence: 99%